Electrify your game! Anodal tDCS increases the resistance to head fakes in basketball - Friehs, M. A.; Güldenpenning, I.; Frings, C.; Weigelt, M. (Journal of Cognitive Enhancement, 2020)
The head fake in basketball describes an action during which players gaze in one direction, but pass the ball to the opposite direction. This deception can be modeled in the lab as a kind of interference resolution task. In such tasks, the left dorsolateral prefrontal cortex (lDLPFC) has been shown to play a critical role. In the present study, transcranial direct current stimulation (tDCS) was used as a form of non-invasive brain stimulation to modify activity in the lDLPFC. In a pre-post design, anodal and cathodal tDCS were contrasted. A 9 cm2 electrode was positioned over the lDLPFC, while a 35 cm2 reference electrode was positioned over the left deltoid. In a sample of N?=?50 healthy, young adults, we observed a trend towards a significant single-session tDCS effect on the head-fake effect. Specifically, it can be argued that anodal tDCS led to enhanced performance by reducing the interference effect produced by head fakes, when compared with cathodal tDCS. This result conforms to previous studies suggesting that neuromodulation of the lDLPFC impacts interference processing. Furthermore, these results bear important implications for the real-life application of tDCS as a tool for cognitive enhancement.